Solar control strategies evaluation in buildings with bioclimatic design-Study Case: Petroleum Engineering School of the Universidad del Zulia - Quirós Lacau, Carlos Enrique (Revista Técnica da Faculdade de Engenharia da de Zulia)
The objective of the present artiele is the design strategies evaluation of solar control in the building group of the Petroleum Engineering School projected by the Venezuelan architect Carlos Raúl Villanueva and built for the Universidad del Zulia in Maracaibo (Venezuela) in the period 1954-1958. For such effects. a planimetric information search, a metric calculation for facades and openings according to the different orientations, a metric site report with its digitalizations of the different solar protection systems and the analysis insolation conditions for the openings with the stereographic solar chart and the shadow protractor was carried out. Through the results of the analysis, it can be evidenced that the original building group of the Petroleum School is an architectural work that is not indifferent to the solar radiation and its effects, since numerous and right solutions are presented front to the solar beams incidence, to avoid the heat excess and the glare in the different enclosures destinated for teaching, research and administrative activities.